La narración como estrategia para mejorar la expresión oral en los niños de 3 y 4 años de la I. E. I. N° 14427 “Santiago Rolando Cano Rivera” Pundín – Huancabamba, 2023. - Flores Quevedo, Zeleni Milagros (2024)
The research conducted at the Educational Institution No. 14427 "Santiago Rolando Cano Rivera" in Pundín, Huancabamba, focused on strengthening the oral expression of 3- and 4-year-old children. It identified initial tensions in the classroom, such as the children's shyness when expressing themselves compared to their communicative freedom during recess, highlighting the need to implement effective pedagogical strategies and integrate families into the educational process. To improve oral expression, an action-research approach was adopted, implementing playful activities such as the use of puppets and storytelling, documented in field journals and analysis matrices. The results showed an improvement in the children's communication, as they autono-mously greeted the teacher and displayed free expression during play. Paren-tal involvement in storytelling activities enriched learning at home, and the af-fectionate environment created by the teacher fostered a safe and respectful atmosphere. The research concludes that the use of playful strategies, family collaboration, and an affectionate approach are essential for the development of oral expression, recommending the continuation of narrative and collabora-tive practices between school and family to optimize the comprehensive devel-opment of children.